Double‐pedicle unaffected split‐breast flap for unilateral breast reconstruction. Issue 5 (5th January 2022) - Satake, Toshihiko; Muto, Mayu; Okamoto, Maki; Onoda, Satoshi; Matsui, Koshi; Narui, Kazutaka; Kobayashi, Shinji; Fujii, Tsutomu; Ishikawa, Takashi; Maegawa, Jiro
Abstract: Background: In some breast cancer patients with a contralateral unaffected hypertrophic and ptotic breast, autologous small‐breast reconstruction with contralateral breast reduction is a good option. The current study is aimed to assess the efficacy of the double‐pedicle unaffected split‐breast (USB) flap harvested from the central half of the unaffected breast for unilateral breast reconstruction with contralateral transverse scar reduction mammoplasty. Methods: Between February 2003 and May 2020, 14 patients underwent breast reconstruction using the USB flap. The mean patient age was 59.1 (range: 48–76) years, and the mean body mass index was 24.2 (range: 19.5–33.3) kg/m 2 . This flap comprised half of the contralateral breast tissues with the 3rd or 4th internal mammary perforator (IMAP) and the lateral thoracic vessel (LTA/V). After USB flap elevation and LTA/V resection, flap perfusion from the IMAP was evaluated on indocyanine green (ICG) angiography. The medial pedicle USB flap was rotated 180° and was transferred to the affected site via the midline. The LTA/V was anastomosed to the recipient vessel to supercharge the distal part of the USB flap, which was then used for breast reconstruction. Then, the remaining contralateral upper and lower breast poles were used for transverse scar reduction mammoplasty. Results: The mean flap size was 13.3 × 26.9 (range: 9.5 × 22 to 16 × 29) cm. All flaps and reduced breasts survived without serious complications such as flap necrosis, although there was one patient with hematoma and one patient with hypertrophic scar. ICG revealed poor perfusion in the distal, lateral part of the flap, ranging from 22.0% to 48.5% of the overall flap area. Final aesthetic evaluation was high, with 11 cases (78.6%) being "good" or "excellent" and 3 cases (21.4%) that were either poor or fair. The mean follow‐up period for the patients was 53.8 (range: 15–84) months, with none of the patients presenting second primary breast cancer or recurrence in both breasts. Conclusion: USB flap breast reconstruction with contralateral reduction mammoplasty is a valuable option in breast cancer patients with a hypertrophic and ptotic breast.